2021
DOI: 10.21203/rs.3.rs-1031824/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID-19 induces neuroinflammation and loss of hippocampal neurogenesis

Abstract: Infection with the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) is associated with onset of neurological and psychiatric symptoms during and after the acute phase of illness1-4. Acute SARS-CoV-2 disease (COVID-19) presents with deficits of memory, attention, movement coordination, and mood. The mechanisms of these central nervous system symptoms remain largely unknown.In an established hamster model of intranasal infection with SARS-CoV-25, and patients deceased from COVID-19, we report a lack … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
56
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 56 publications
6
56
0
3
Order By: Relevance
“…While that study analyzed hospitalized patients, we evaluated individuals that did not require hospitalization (i.e., had mild respiratory symptoms); nonetheless, we observed notable alterations in cortical thickness. Importantly, some of these alterations correlated with the severity of symptoms of anxiety and impaired cognition, which is consistent with previous literature 51,74,75 .…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While that study analyzed hospitalized patients, we evaluated individuals that did not require hospitalization (i.e., had mild respiratory symptoms); nonetheless, we observed notable alterations in cortical thickness. Importantly, some of these alterations correlated with the severity of symptoms of anxiety and impaired cognition, which is consistent with previous literature 51,74,75 .…”
Section: Discussionsupporting
confidence: 91%
“…Our study demonstrates structural and functional alterations in the brain tissue of COVID-19 patients which correlate with neuropsychiatric and neurological dysfunctions. This study and other reports showing alterations in brain structure and the manifestation of neurological symptoms in COVID-19 patients 4951 raise a debate on whether these clinical features are a consequence of peripheral changes or the potential ability of the virus to invade the CNS. Our findings support the latter, at least in part, as we detect SARS-CoV-2 in brain tissue collected from patients who died of COVID-19.…”
Section: Discussionmentioning
confidence: 52%
“…Central cytokines and chemokines play a role in inducing hyperalgesia and allodynia, while a sustained increase leads to chronic widespread pain at several body locations, suggesting that neuroinflammation drives widespread chronic pain through central sensitisation [ 47 ]. Therefore, neuroinflammation is expected to play a role in persisting symptoms after COVID-19 infection as well [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…Histopathological analyses of SARS-CoV-2 infected primates identified evidence of neuronal death [ 67 ]. Two publications demonstrated that rodent models of acute COVID-19 exhibit decreased neurogenesis in the dentate gyrus region of the hippocampus and a loss of myelination in subcortical white matter tracts, with the former study confirming loss of neurogenesis in humans [ 22 , 68 ]. Multiple post-mortem studies of human and primate tissue noted increased GFAP staining, but more data is needed to understand alterations in astrocyte function and the sources of astrocyte activation [ 41 , 42 ].…”
Section: Cns Resident Immunity and Sars-cov-2mentioning
confidence: 99%